Citizenship and Democratization in Southeast Asia - Berenschot, Ward; Schulte Nordholt, Henk; Bakker, Laurens (Social, Economic and Political Studies of the Middle East and Asia, 2016)
By providing various fascinating first-hand accounts of how citizens negotiate their rights in the context of weak state institutions, Citizenship and Democratization in Southeast Asia offers a unique bottom-up perspective on the evolving character of public life in democratizing Southeast Asia. Readership: All interested in politics and governance in Southeast Asia, as well as scholars concerned with citizenship in postcolonial states.